2014
DOI: 10.1002/anie.201400957
|View full text |Cite
|
Sign up to set email alerts
|

Significant Improvements in CO2 Capture by Pyridine‐Containing Anion‐Functionalized Ionic Liquids through Multiple‐Site Cooperative Interactions

Abstract: A strategy for improving CO2 capture by new anion-functionalized ionic liquids (ILs) making use of multiple site cooperative interactions is reported. An extremely high capacity of up to 1.60 mol CO2 per mol IL and excellent reversibility were achieved by introducing a nitrogen-based interacting site on the phenolate and imidazolate anion. Quantum-chemical calculations, spectroscopic investigations, and calorimetric data demonstrated that multiple-site cooperative interactions between two kinds of interacting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
187
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 297 publications
(198 citation statements)
references
References 67 publications
10
187
1
Order By: Relevance
“…[4,7,8] This is mainly owed to the high CO 2 solubility in ILs as well as the possibility to fine-tune the sorption properties of the ionic material. [16][17][18][19][20][21] This mechanism requires much more energy for CO 2 release than the noncovalent path, but because of the formation of a CO 2 derivative, these ILs have in turn ah igherc apacity for CO 2 capture. [9,10] However,t he use of traditional and neat ILs as physicals orbents for CO 2 is not particularly good because, in most of the cases, their noticeable high solubility resultsf rom their high molecular weight.…”
Section: Introductionmentioning
confidence: 99%
“…[4,7,8] This is mainly owed to the high CO 2 solubility in ILs as well as the possibility to fine-tune the sorption properties of the ionic material. [16][17][18][19][20][21] This mechanism requires much more energy for CO 2 release than the noncovalent path, but because of the formation of a CO 2 derivative, these ILs have in turn ah igherc apacity for CO 2 capture. [9,10] However,t he use of traditional and neat ILs as physicals orbents for CO 2 is not particularly good because, in most of the cases, their noticeable high solubility resultsf rom their high molecular weight.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, CO 2 capture and storage (CCS) has emerged due to its massive removal of CO 2 and the connectivity with a fossil fuel based process. [8][9][10][11][12] A promising alternative for CO 2 capture from ue gas is to utilize porous solid sorbents based on pressure, vacuum or temperature swing systems relying on its low energyconsumption and adsorption-sensitivity on temperature and pressure. 3 CO 2 capture and storage technologies primarily include precombustion (CO 2 /H 2 ), post-combustion (CO 2 /N 2 ), and oxycombustion.…”
Section: Introductionmentioning
confidence: 99%
“…To verify this speculation, 13 36 and after CO 2 bubbling, this peak was split into two peaks Figure S6). Thus the structural transition in the IL self-assemblies 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 shown that the pH value change also did not noticeably affect the size of the IL self-assembly (see Figure S7).…”
Section: Possible Mechanism For Co 2 -Driven Structural Transition Ofmentioning
confidence: 99%